Characteristics of Patients With Knee Osteoarthritis Treated With Total Knee Arthroplasty and Conservative Treatment at Kustati Islamic General Hospital Surakarta From January 2024 to September 2025 - Bramasta Agra Sakti; Zuhad Irfan; Fajar Baskoro Gardjito (Lembaga Pengembangan Kinerja Dosen, 2026)
This study aims to research the characteristics of patients with knee osteoarthritis who received total knee arthroplasty and conservative treatment at Kustati Islamic General Hospital from January 2024 to September 2025. This research uses the cross-sectional retrospective approach with the descriptive method. The research subjects comprise patients with knee osteoarthritis who have undergone total knee arthroplasty at Kustati Islamic General Hospital from January 2024 to September 2025, as well as those who have received conservative treatment during the same timeframe at Kustati Islamic General Hospital. The majority of patients undergoing total knee arthroplasty were female (75.79%) and belonged to the age range of 56-65 years (52.6%). The Body Mass Index of patients undergoing total knee arthroplasty predominantly falls within the overweight category, comprising 42.1% of the population. The majority of patients receiving conservative treatment were female (80.76%). Additionally, the age group of 56-65 years constituted 39.4%. The majority of patients with knee osteoarthritis undergoing total knee arthroplasty and conservative therapy are female, predominantly aged 56 to 65 years. The body mass index of individuals undergoing total knee arthroplasty predominantly falls within the overweight category.